2000
DOI: 10.1128/aac.44.1.131-133.2000
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effects of Liposomal Amphotericin B and Conventional Amphotericin B on Propafenone Metabolism and Hepatic Cytochrome P-450 in Rats

Abstract: The effects of conventional amphotericin B (AmB) dissolved in sodium deoxycholate on microsomal cytochrome P-450 concentrations and propafenone metabolism to 5-hydroxy-propafenone and N-desalkylpropafenone were compared with those of liposomal AMB (Li-AMB) in rats. AmB (3 mg/kg/day, intravenously [i.v.]) given for 4 days caused a significant decrease in the concentration of hepatic microsomal cytochrome P-450 (0.43 ؎ 0.06 nmol/mg versus 0.62 ؎ 0.05 nmol/mg for the control [P < 0.05]). Following the application… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…Inaddition,othermeasured parameters related todrugmetabolizing enzyme systemsw erenotchanged significantlycompared withthosei nthe control group. Itw as previouslyr eported thatD-AMB, but notL-AMB, influ-encesmicrosomalCYP concentrationsin rats,whichi s consistentw itho ur presentr esults [28].Inf act,in human,interactionsbetween L-AMB and co-administered drugswithregardtodrug-metabolizing enzyme systems haven otbeen reported,whichwass upported byour presents tudy.…”
Section: Antibiotics•antimycotics•antiparasitics•antiviraldrugs•chemosupporting
confidence: 87%
“…Inaddition,othermeasured parameters related todrugmetabolizing enzyme systemsw erenotchanged significantlycompared withthosei nthe control group. Itw as previouslyr eported thatD-AMB, but notL-AMB, influ-encesmicrosomalCYP concentrationsin rats,whichi s consistentw itho ur presentr esults [28].Inf act,in human,interactionsbetween L-AMB and co-administered drugswithregardtodrug-metabolizing enzyme systems haven otbeen reported,whichwass upported byour presents tudy.…”
Section: Antibiotics•antimycotics•antiparasitics•antiviraldrugs•chemosupporting
confidence: 87%
“…Because amphotericin B is not soluble in water, it is prepared as a mixture of amphotericin B and the bile salt deoxycholate or as a liposomal formulation. Although a previous study showed that the liposomal formulation did not alter cytochrome P450, the deoxycholate alone appeared to disturb hepatic metabolism (74). The preparation of amphotericin B that we used in our studies was also the water-soluble deoxycholate formulation (Fungizone).…”
Section: Discussionmentioning
confidence: 99%
“…Vice versa, selective inhibition of CYP450 enzymes was observed in rats treated with D-AMB, assumed to be due to an impairment of monooxygenases on the endoplasmic reticulum [ 106 ]. This inhibitory effect on CYP450 activity was confirmed in humans [ 107 ].…”
Section: Specific Patient Populationsmentioning
confidence: 99%